TANGGUNG JAWAB RUMAH SAKIT TERHADAP PASIEN PADA PELAYANAN INSTALASI GAWAT DARURAT DI RUMAH SAKIT DR. CIPTO MANGUNKUSUMO BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Angga Kurniansyah; Rineke Sara (Fakultas Hukum Universitas Borobudur, 2024)
The position of hospitals as providers of health services and patients as recipients of health services in health facilities has been regulated in Law Number 17 of 2023 concerning Health which aims to increase awareness, willingness, and ability to live healthily for the community. This study discusses the responsibility of hospitals towards patients who experience losses in the Emergency Room services of Dr. Cipto Mangunkusumo Hospital and the efforts made by patients who are harmed by the Emergency Room services of Dr. Cipto Mangunkusumo Hospital. This study uses a normative legal approach method that is empirical in nature. The results of the study indicate that the responsibility of hospitals towards patients in the Emergency Room services of Dr. Cipto Mangunkusumo Hospital is due to inadequate health services, not in accordance with the rules and procedures, and can cause losses to patients. The hospital will provide health services until the patient recovers. If a patient is harmed, the patient can file a complaint with the professional ethics council, request compensation through a lawsuit for unlawful acts, or file a civil lawsuit for losses incurred due to the negligence of medical personnel on duty in the Emergency Room as regulated in Article 1367 of the Civil Code, Article 304 of the Criminal Code, and Article 531 of the Criminal Code.